1999
DOI: 10.1016/s0048-9697(99)00398-8
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in blood collected from birds feeding in the area around Doñana National Park affected by the toxic spill from the Aznalcóllar mine

Abstract: A long-term monitoring plan was established to study if bird populations around Doñana National Park were affected by the toxic spill from the Aznalcóllar mine. The concentrations of Zn, Pb, As, Cu, Sb, Co, Tl and Cd in the blood of 11 bird species feeding in the area were determined. The parameters which most affect the accumulation of trace elements in the birds studied are, firstly, species and secondly, trophic position, sex, days of exposure and weight. In some individuals, Zn and Cu occurred at higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
3
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 29 publications
2
34
3
2
Order By: Relevance
“…However, Havera et al (1992) also found higher PbB levels in male lesser scaup (Aythya affinis), but this difference was not observed for Pb shot ingestion. Higher PbB levels were also observed in males of several species of birds from Doñ ana National Park after an accidental mine spill (Benito et al, 1999). In our study, it is possible that male mallards had spent longer at Medina than females, as they may move to the lagoon to moult while females are still rearing their broods at other wetlands.…”
Section: Blood Pb Blood Concentration and Alad Activitymentioning
confidence: 52%
“…However, Havera et al (1992) also found higher PbB levels in male lesser scaup (Aythya affinis), but this difference was not observed for Pb shot ingestion. Higher PbB levels were also observed in males of several species of birds from Doñ ana National Park after an accidental mine spill (Benito et al, 1999). In our study, it is possible that male mallards had spent longer at Medina than females, as they may move to the lagoon to moult while females are still rearing their broods at other wetlands.…”
Section: Blood Pb Blood Concentration and Alad Activitymentioning
confidence: 52%
“…(mg/l; except 2n: mg/ml) and range in parentheses; n=11 for Cu and 26 in all other cases: Cu=0.472 T 0.110 (0.260-0.717); Cd=1.134 T 0.804 (0.200-3.849); Zn=3.615 T 0.655 (2.559-4.467); Pb=146.0 T 293.8 (not detected-1780.0); As=18.88 T 27.44 (not detected-42.30). The levels producing sub-lethal effects are unknown for Cu, Cd, Zn, and As, but according to Benito et al (1999) values of Cu and Zn from Canary Egyptian vultures were well below those found in birds living in areas with contamination. In addition, values of Cd and As were those considered as normal in non-polluted zones (1 mg/ l and 20 mg/l respectively); values surpassing those levels were never as high as those found in polluted regions.…”
Section: Heavy Metal Contaminationmentioning
confidence: 84%
“…Benito et al, 1999). Analyses of Zn and Cu were performed by Flame Atomic Absorption Spectrometer (AAS).…”
Section: Heavy Metal Analysesmentioning
confidence: 99%
“…DOI 10.1002/em Determination of lead, cadmium, and arsenic in heparinized blood specimens was performed by Graphite Furnace Atomic Absorption Spectrometry (GFAAS) with Zeeman-effect background correction, using the method of standard addition [Benito et al, 1999]. In the case of mercury, analysis was performed using Cold Vapor Atomic Absorption Spectrometry (CVAAS).…”
Section: Methodsmentioning
confidence: 99%